How Fast-Fashion Brands Changed Garment Industry Landscape: Study Case On Relationship Of Garment Factories And Sewing Thread Suppliers In Jakarta, Banten And West Java - Pamungkas, Ryzky; Balqiah, Tengku Ezni (Ilomata International Journal of Management, 2025)
The garment industry is currently facing considerable challenges in meeting the demands of overseas buyers. The fast fashion trend has shortened garmen production cycles and forced garmen factories to work with reliable suppliers, especially sewing thread suppliers, to fulfil the production needs of garmen factories in a short period of time. This research emphasises the importance of building strategic partnerships between garmen factories and sewing thread suppliers within the framework of B2B marketing relationships to ensure an effective and sustainable supply chain. Previous research states that there is a positive influence between commitment, trust, and relative dependence on customer satisfaction and customer loyalty in distributor and seller relationships. This study builds a model to further analyse the influence of Affective Commitment, Instrumental Commitment, Capability-based Trust, Benevolence-based Trust, and Relative Dependence factors to achieve customer satisfaction and customer loyalty in the relationship between garmen factories and sewing thread suppliers. The research method used is quantitative method with data collection through surveys sent to garmen factories located in Banten, West Java, and DKI Jakarta Provinces. Data analysis was conducted using SmartPLS to determine the relationship between the research variables.The findings of this study state that Affective Commitment, Instrumental Commitment, Capability-based Trust, and Benevolence-based Trust can increase customer satisfaction and customer loyalty, but relative dependence was found to have no significant effect on customer satisfaction and customer loyalty. These findings provide new insights for companies in developing their business strategies.